Defining new clinically derived criteria for high disease activity in non-systemic juvenile idiopathic arthritis: a Finnish multicentre study - Maria Backström; Pirjo Tynjälä; Kristiina Aalto; Heikki Ylijoki; Anne Putto-Laurila; Minna-Maija Grönlund; Johanna Kärki; Paula Keskitalo; Sirja Sard; Heini Pohjankoski; Maiju Hietanen; Silke Witter; et al. (Oxford University Press, 2022)
Objectives
To redefine criteria for high disease activity (HDA) in JIA, to establish HDA cut-off values for the 10-joint Juvenile Arthritis Disease Activity Score (JADAS10) and clinical JADAS10 (cJADAS10) and to describe the distribution of patients’ disease activity levels based on the JADAS cut-off values in the literature.
Methods
Data on 305 treatment-naïve JIA patients were collected from nine paediatric units treating JIA. The median parameters of the JADAS were proposed to be the clinical criteria for HDA. The cut-off values were assessed by using two receiver operating characteristics curve–based methods. The patients were divided into disease activity levels based on currently used JADAS cut-off values.
Results
We proposed new criteria for HDA. At least three of the following criteria must be satisfied in both disease courses: in oligoarthritis, two or more active joints, ESR above normal, physician global assessment (PGA) of disease activity ≥2 and parent/patient global assessment (PtGA) of well-being ≥2; in polyarthritis, six or more active joints, ESR above normal, PGA of overall disease activity ≥4 and PtGA of well-being ≥2. The HDA cut-off values for JADAS10 (cJADAS) were ≥6.7 (6.7) for oligoarticular and ≥15.3 (14.1) for polyarticular disease. The distribution of the disease activity levels based on the JADAS cut-off values in the literature varied markedly based on which cut-offs were used.
Conclusion
New clinically derived criteria for HDA in JIA and both JADAS and cJADAS cut-off values for HDA were proposed.